Urolithin B suppresses tumor growth in hepatocellular carcinoma through inducing the inactivation of Wnt/β‐catenin signaling - Lv, Min‐yi; Shi, Chuan‐jian; Pan, Fei‐fei; Shao, Jiang; Feng, Lu; Chen, Guoqin; Ou, Caiwen; Zhang, Jin‐fang; Fu, Wei‐ming (Journal of cellular biochemistry, 2019)
Consumption of dietary ellagitannins (ETs) has been proven to benefit multiple chronic health disorders including cancers and cardiovascular diseases. Urolithins, gut microbiota metabolites derived from ETs, are considered as the molecules responsible for these health effects. Previous studies have demonstrated that urolithins exhibit antiproliferative effects on prostate, breast, and colon cancers. However, as for hepatocellular carcinoma (HCC), it remains elusive. Herein, we aim to investigate the function of urolithin B (UB), a member of urolithins family, in HCC. The effects of UB on cell viability, cell cycle and apoptosis were evaluated in HCC cells, and we found UB could inhibit the proliferation of HCC cells, which resulted from cell cycle arrest and apoptosis. Furthermore, UB could increase phosphorylated β‐catenin expression and block its translocation from nuclear to cytoplasm, thus inducing the inactivation of Wnt/β‐catenin signaling. Using a xenograft mice model, UB was found to suppress tumor growth in vivo. In conclusion, our data demonstrated that UB could inhibit the proliferation of HCC cells in vitro and in vivo via inactivating Wnt/β‐catenin signaling, suggesting UB could be a promising candidate in the development of anticancer drugs targeting HCC. We firstly reported that UB, the gut metabolites of ETs, suppress tumorigenesis of HCC in vitro and in vivo via inactivating Wnt/β‐catenin signaling.